2017
DOI: 10.1038/s41598-017-05602-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of VAMP2 Alters Morphology of the Tegument and Affects Glucose uptake, Development and Reproduction of Schistosoma japonicum

Abstract: Schistosomiasis caused by schsitosomes is a serious global public health concern. The tegument that surrounds the worm is critical to the schistosomes survival. The tegument apical membrane undergoes a continuous process of rupture and repair owing to membranous vacuoles fusing with the plasma membrane. Vesicle-associated membrane protein 2 (VAMP2), a member of soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNAREs) is required for membrane fusion. Here, we used RNA interference (RNAi) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Interestingly, three phosphorylated proteins identified in Cluster 10 are involved in SNARE interactions during vesicular transport and thus might play an important part in the successful delivery of vesicles to the schistosome surface to replenish/modify the host-interactive surface layer of the parasite which turns over in vivo. In this context, the SNARE family member vesicle associated membrane protein 2 (VAMP2) was recently found to play a likely role in tegument maintenance, glucose uptake and egg production in S. japonicum [81]. Moreover, because the contents of schistosomederived extracellular vesicles [82,83] have recently been found to modulate host immune cells to support parasite survival [84,85], developing an understanding of vesicle trafficking mechanisms in these worms is a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three phosphorylated proteins identified in Cluster 10 are involved in SNARE interactions during vesicular transport and thus might play an important part in the successful delivery of vesicles to the schistosome surface to replenish/modify the host-interactive surface layer of the parasite which turns over in vivo. In this context, the SNARE family member vesicle associated membrane protein 2 (VAMP2) was recently found to play a likely role in tegument maintenance, glucose uptake and egg production in S. japonicum [81]. Moreover, because the contents of schistosomederived extracellular vesicles [82,83] have recently been found to modulate host immune cells to support parasite survival [84,85], developing an understanding of vesicle trafficking mechanisms in these worms is a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Five sets of experiments were designed for each of three developmental stages of E. granulosus : (1) no-treatment group without any RNAi intervention, (2) unrelated/irrelevant Negative Control siRNA (siR-Ctrl) group that was transfected into the parasites using three transfection techniques i.e. soaking, electroporation and electro-soaking, (3) EgCaM-specific siRNA group delivered by soaking, (4) EgCaM-specific siRNA group delivered by electroporation and (5) EgCaM-specific siRNA group delivered by electro-soaking 13,14,21,49 . EgCaM-specific and Negative Control siRNAs were delivered into the parasites of corresponding treatment groups using three transfection techniques.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that, in addition to host insulin, schistosome IRs can also bind to the schistosome insulin-like peptide, thereby activating the worm’s insulin pathway [ 68 ]. Further studies confirmed that vesicle-associated membrane protein 2 (VAMP2) knockdown significantly affected the transcript levels of SGTP1 , SGTP4 , and insulin receptors ( IR1 and IR2 ) [ 69 ]. In female worms, vamp2 RNAi mainly caused a reduction in egg production [ 69 ], which may be influenced by impaired energy access in males [ 70 ].…”
Section: Mechanism Of Nutrient Intake and Utilizationmentioning
confidence: 97%
“…Further studies confirmed that vesicle-associated membrane protein 2 (VAMP2) knockdown significantly affected the transcript levels of SGTP1 , SGTP4 , and insulin receptors ( IR1 and IR2 ) [ 69 ]. In female worms, vamp2 RNAi mainly caused a reduction in egg production [ 69 ], which may be influenced by impaired energy access in males [ 70 ].…”
Section: Mechanism Of Nutrient Intake and Utilizationmentioning
confidence: 97%
See 1 more Smart Citation